2016
DOI: 10.1016/j.ceramint.2016.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Improving hole exit quality in rotary ultrasonic machining of ceramic matrix composites using a compound step-taper drill

Abstract: Mechanical-machining-induced tearing defects at hole exits restrict the application of C/SiC composites. Rotary ultrasonic machining (RUM) is suitable for hole manufacture in brittle composites, providing reduced tearing size as compared with conventional grinding. Even so, substantial tearing defects at the hole exit remain with RUM. In this study, a novel compound steptaper diamond core drill for RUM of C/SiC was developed to further improve the hole exit quality. Contrastive machining tests were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 20 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Figure 8a and Figure 8b show the three mechanisms that form the exit delamination (i.e. tearing, burring and edge chipping) and the influence that this damages have depending on the fibre orientation [32], [33]. Several authors [34]- [37] concluded that Rotary Ultrasonic Machining (RUM) produced an overall lower thrust force (≈10-15% [34]) which was translated to a less significant exit delamination.…”
Section: Figure 7 Influence Of the Fibre Orientation When Drilling Perpendicular And Tilted Holes In Orthotropic Materials Such As Cmcsmentioning
confidence: 99%
“…Figure 8a and Figure 8b show the three mechanisms that form the exit delamination (i.e. tearing, burring and edge chipping) and the influence that this damages have depending on the fibre orientation [32], [33]. Several authors [34]- [37] concluded that Rotary Ultrasonic Machining (RUM) produced an overall lower thrust force (≈10-15% [34]) which was translated to a less significant exit delamination.…”
Section: Figure 7 Influence Of the Fibre Orientation When Drilling Perpendicular And Tilted Holes In Orthotropic Materials Such As Cmcsmentioning
confidence: 99%
“…There are issues with ultrasonic machining also, such as due to stress concentration at the periphery of the hole exit a fracture at the edges occurs [19]. Wang et al [20] employed a unique blended step-taper diamond core drill for RUM of C/ SiC to enhance the hole exit accuracy. The results indicated that the compound drill could be useful to minimize the tearing size by thirty percent.…”
Section: Introductionmentioning
confidence: 99%
“…Kumaran et al [12] inferred reduced burr at hole exit at the expense of increased thrust force in RUD of CFRP composite under low temperature conditions. Wang et al [28] addressed the reduction in tearing size and drilling forces due to reprocessing effect of compound step drill during RUD of C/SiC. During RUD of quartz glass and sapphire, Wang et al [29] reported 60% reduction in edge chipping with step drills having step thickness smaller than the thickness of drill end face.…”
Section: Introductionmentioning
confidence: 99%